Elasticity of Marginal Utility of Consumption: The Equal-Sacrifice Approach Applied for the Czech Republic - Matej Opatrny; Milan Scasny (Charles University in Prague, Institute of Economic Studies (IES), 2021)
We provide the first estimate of the elasticity of marginal utility of consumption, η, for a post-transition economy in the Central & Eastern European region, the Czech Republic, based on individual-level data. The parameter η is a crucial component of the social discount rate (SDR), which determines the inter-temporal allocations that are acceptable to society. Using the equal-sacrifice income tax approach, we obtain a central estimate of η at 1.34, which varies between 1.24 and 1.42 within the study period that covers 2005-2019. Moreover, the estimate of elasticity of marginal utility of consumption differs between various income groups and employment status. Importantly, the magnitude of η estimate depends on whether social benefits are included into gross income or social and health insurance payments are included in the definition of taxes. Our results suggest that SDR for the Czech Republic may be around 3-5 percent for a reasonable pure rate of time preference and positive forecast for per capita consumption growth.
Keywords: D60; D61; H24; R13; 330; elasticity of marginal utility of consumption; equal-sacrifice approach; income tax schedules; marginal tax rate; social discount rate